Upaya Meningkatkan Motivasi Belajar Menggunakan Media Puzzle - Safitri, Violetta; Putri, Rahma Evita; Yenira, Fitria (Lembaga Yasin AlSys, 2025)
Teachers hold a critical responsibility in creating engaging learning experiences through innovative pedagogical approaches, one of which is the use of instructional media to stimulate student participation and foster interest, enjoyment, motivation, and curiosity. This study aims to evaluate the effectiveness of instructional media in enhancing student activity and motivation. A mixed-methods approach was employed, collecting qualitative data through direct observation and interviews, and quantitative data through student performance assessments. The researcher was directly involved in the teaching process of Class VIII to gain contextual understanding of student behaviors and responses during learning. Observation results indicate that in Cycle I, student participation reached 60% in the first session and 72% in the second session, with an average of 66%. In Cycle II, there was a significant increase, with 80% participation in the first session and 96% in the second, averaging 92%. These findings demonstrate that the consistent use of instructional media can gradually enhance student participation and learning activity. Therefore, integrating media as part of a cycle-based instructional strategy is effective in creating an interactive and motivating learning environment.